2013
DOI: 10.1248/cpb.c12-00823
|View full text |Cite
|
Sign up to set email alerts
|

Statistical modeling, optimization and characterization of spray-dried solid self-microemulsifying drug delivery system using design of experiments

Abstract: The present study systematically and simultaneously investigates the influence of process variables of spray-drying on the properties of solid self-microemulsifying drug delivery system (SmeddS) using design of experiment (DOE) and optimizes them in order to produce solid-SMEDDS satisfying pre-defined powder quality attributes. Flurbiprofen-loaded liquid-SMEDDS was dispersed in dextran and spray-dried. After preliminary screening, the independent factors selected according to three-factor, three-level Box-Behn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 29 publications
(26 reference statements)
0
9
0
Order By: Relevance
“…Finally, adequate precision is a measure of the experimental signal to noise ratio. The adequate precision scored 24.848, a value higher than the critical value of 4, indicating high signal to noise ratio and sufficiency of the model to navigate the experimental space (Zhang and Youan, 2010;Marasini et al, 2013;Abdel-Hafez et al, 2014). Consequently, the model could be utilized for GNPs size optimization and prediction.…”
Section: Optimization Of the Prepared Gnpsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, adequate precision is a measure of the experimental signal to noise ratio. The adequate precision scored 24.848, a value higher than the critical value of 4, indicating high signal to noise ratio and sufficiency of the model to navigate the experimental space (Zhang and Youan, 2010;Marasini et al, 2013;Abdel-Hafez et al, 2014). Consequently, the model could be utilized for GNPs size optimization and prediction.…”
Section: Optimization Of the Prepared Gnpsmentioning
confidence: 99%
“…Additionally, in order to investigate the effect of formulation variables on responses (dependent variables), BBD exclude simultaneous implementation of variables at their maximum or minimum levels, thereby the design points are selected as middle value for one factor and maximum or minimum for the other factors. By avoiding corners in the design space, BBD provides safety in its experiments setting (Marasini et al, 2013). Accordingly, DoE could contribute to enhanced quality attributes of the final product and cost and time reduction of the formulation process (Zhang and Youan, 2010;Marasini et al, 2013;Abdel-Hafez et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The air pressure was 4 kg/cm 2 , and aspiration was set at 80%, which indicated that the pressure of the aspirator filter vessel was −30 mbar. The direction of air flow was the same as that of the sprayed product (27,28,31,33,35). The physical mixtures of erlotinib and carriers were prepared by mixing erlotinib and each carrier with the same weight ratio in the solid SEDDS formulations.…”
Section: Preparation Of Erlotinib-loaded Solid Seddsmentioning
confidence: 99%
“…However, although these systems have some advantages over emulsions, compared to solid dosage forms, there are still some practical drawbacks associated with the conventional (liquid) SEDDS, including storage instability and interaction with hard or soft capsules. Solidification of liquid SEDDS has been used increasingly in an effort to overcome the abovementioned limitations and combine the advantages of conventional lipid-based drug delivery systems (i.e., increased solubility and bioavailability) with those of solid dosage forms (e.g., high stability and reproducibility, ease of process control, and relatively low production cost) (26)(27)(28)(29)(30)(31)(32)(33)(34).…”
Section: Introductionmentioning
confidence: 99%